TGF-β Repressors SnoN and Ski Are Implicated in Human Colorectal Carcinogenesis - Vasiliki Bravou; Anna Antonacopoulou; Helen Papadaki; Konstantina Floratou; Michalis Stavropoulos; Vasso Episkopou; Chariklia Petropoulou; Haralabos Kalofonos (Cellular Oncology)
Background: The TGF-β signaling repressors SnoN and Ski have been critically implicated in human cancer.